Makna Simbol Komunikasi Ritual Pada Tradisi Badudus Suku Banjar - Hidayah, Maulida (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2023)
The The badudus tradition is a tradition that is usually carried out before the traditional marriage ceremony of the Banjar tribe. The badudus tradition is a custom or habit that has been passed down by the ancestors since ancient times and continues to be practiced today. This paper aims to examine the ritual communication of the badudus tradition in the Banjar tribe of South Kalimantan, especially Tabalong district. This paper uses field research and a descriptive-qualitative approach. Data sources were obtained through interviews with cultural, religious, and community leaders as tradition actors. This paper finds the Badudus tradition not only as a physical self-cleansing, but also inwardly. This paper also explains the meaning of the materials used in the Badudus tradition. The communication model used in the Badudus tradition is a sacred ceremony where people gather to follow a series of Badudus tradition events. The Badudus tradition in the process of implementation still needs further study because there are still several things that need to be refined which aims to make the implementation of the Badudus tradition in accordance with Islamic religious law. One of them is the intention to carry out the badudus tradition which aims to keep away from all calamities, making this tradition need changes in terms of intention, and the implementation of the badudus tradition in the future must be more directed towards Islamic values so that its implementation is in accordance with Islamic religious law.